Characterisation of a novel cellobiose 2‐epimerase from thermophilic Caldicellulosiruptor obsidiansis for lactulose production. (30th December 2016) - Chen, Qiuming; Levin, Roman; Zhang, Wenli; Zhang, Tao; Jiang, Bo; Stressler, Timo; Fischer, Lutz; Mu, Wanmeng
Abstract: BACKGROUND: Lactulose, a bioactive lactose derivative, has been widely used in food and pharmaceutical industries. Isomerisation of lactose to lactulose by cellobiose 2‐epimerase (CE) has recently attracted increasing attention, since CE produces lactulose with high yield from lactose as a single substrate. In this study, a new lactulose‐producing CE from Caldicellulosiruptor obsidiansis was extensively characterised. RESULTS: The recombinant enzyme exhibited maximal activity at pH 7.5 and 70 °C. It displayed high thermostability with T m of 86.7 °C. The half‐life was calculated to be 8.1, 2.8 and 0.6 h at 75, 80, and 85 °C, respectively. When lactose was used as substrate, epilactose was rapidly produced in a short period, and afterwards both epilactose and lactose were steadily isomerised to lactulose, with a final ratio of 35:11:54 for lactose:epilactose:lactulose. When the reverse reaction was investigated using lactulose as substrate, both lactose and epilactose appeared to be steadily produced from the start. CONCLUSION: The recombinant CE showed both epimerisation and isomerisation activities against lactose, making it an alternative promising biocatalyst candidate for lactulose production. © 2016 Society of Chemical Industry